Phenylephrine, a common cold remedy active ingredient, suppresses uterine contractions through cAMP signalling - Chen, Xingjuan (Sci Rep, 2018)
Regulation of uterine contractility is an important aspect of women’s health. Phenylephrine, a selective agonist of the α(1)-adrenoceptor and a potent smooth muscle constrictor, is widely used in women even during pregnancy to relieve cold-related symptoms, to treat postpartum haemorrhoid, and during routine eye exams. We performed isometric tension recordings to investigate the effect of phenylephrine on mouse uterine contractility. Phenylephrine decreased spontaneous and oxytocin-induced contractions in non-pregnant mouse uterine rings and strips with an IC(50) of ~1 μM. Prazosin, an inhibitor of α(1)-adrenoceptor, did not prevent phenylephrine-mediated relaxations. Conversely, ICI118551, an antagonist of β2-adrenoceptors, inhibited phenylephrine relaxation. In the presence of ICI118551, high concentrations (>30 μM) of phenylephrine caused mouse uterine contractions, suggesting that β-adrenoceptor-mediated inhibition interferes with the phenylephrine contractile potential. Phenylephrine-dependent relaxation was reduced in the uterus of pregnant mice. We used primary mouse and human uterine smooth muscle cells (M/HUSMC) to establish the underlying mechanisms. Phenylephrine stimulated large increases in intracellular cAMP in M/HUSMCs. These cAMP transients were decreased when HUSMCs were cultured in the presence of oestrogen and progesterone to mimic the pregnancy milieu. Thus, phenylephrine is a strong relaxant in the non-pregnant mouse uterus, but exhibits diminished effect in the pregnant uterus.